Morbimortalidade em indivíduos vacinados contra a Covid-19 na Bahia - Correia, Thaísa Mercês de Oliveira (2023)
The emergence of COVID-19 and its complications, along with the immediate preventive action through vaccination, has been the subject of study since the pandemic was declared in 2020, during which thousands of lives were lost worldwide. In Bahia, over one million people were infected by SARS-CoV-2, and more than 31 thousand deaths occurred due to the disease. The vaccine has been available since January 2021 as a means to combat, particularly, morbidity and mortality among severe and critical cases caused by the disease. The objectives of this study were to assess the occurrence of severe COVID-19 in individuals hospitalized for Severe Acute Respiratory Syndrome (SARS) and vaccinated against COVID-19 from January 2021 to August 2022. The study aimed to describe the clinical characteristics of the cases, outline the vaccination schedules among individuals who experienced severity and death, estimate the case fatality rate, and identify predisposing risk factors in vaccinated individuals who developed severe outcomes. This study is characterized as a retrospective cohort based on secondary data from the Influenza Epidemiological Surveillance Information System (SIVEP- Gripe). After establishing inclusion and exclusion criteria, the study's sample consisted of 9,904 cases. Descriptive analyses revealed that the population segment with the highest frequency of cases included males, the elderly, individuals with comorbidities, those with symptoms such as cough, fever, dyspnea, respiratory discomfort, and desaturation, who were admitted to the intensive care unit (ICU), and required ventilatory support. The highest fatality rates were observed in females, the elderly, individuals of indigenous and mixed race, those with no formal education, individuals residing in rural areas, those admitted to the ICU, and those requiring invasive ventilatory support. The variable related to the COVID-19 vaccine should be approached with caution, as it was a limitation of this study, considering that integration with the National Vaccination Database only occurred in 2022. Given the significant relevance of this study and considering the importance of vaccination in mitigating severe events, it is crucial to continue strengthening vaccination strategies. Additionally, there should be awareness among healthcare workers about the importance of accurately recording information in the system to ensure data quality.